GEBELİKTE SOLUNUM FİZYOLOJİSİ - TETİKKURT, Cüneyt (Cerrahpaşa Medical Journal, 2014)
Background.- Pregnancy causes significant consequences in respiratory physiology. To support fetal life normal parameters of laboratory tests undergo a dynamic and significant change during pregnancy. Evaluation of pulmonary disease states occurring during or that has been present before pregnancy requires a through comprehension of maternal respiratory physiology. In this review, the respiratory physiologic changes with consequences on pulmonary function have been discussed.